MONITORING POPULASI NYAMUK Aedes aegypti L. VEKTOR PENYAKIT DEMAM BERDARAH DENGUE DI KELURAHAN GEDONGKIWO KECAMATAN MANTRIJERON KOTA YOGYAKARTA - Sukesi, Tri Wahyuni (Universitas Ahmad Dahlan, 2012)
Background: Gedongkiwo Village is one of the villages that was ranked first for the highestnumber of dengue disease in the year 2010. Many years in the urban village health centerssupported Gedongkiwo local government has sought to control the vector mosquito Ae.aegyptiL, but such efforts until now have not shown significant results. Outreach efforts and thepromotion of public health for more attention to hygiene and environmental health are also ableto reduce the incidence of DHF has not been clearly defined. On the other hand, anotherproblem arises, namely the occurrence of resistance in mosquitoes Ae.aegypti L. of thepesticide compound that is used for eradication. The purpose of this study was to Knowing thepopulation of mosquito species Ae. Aegypti L. If visits by the House Index (HI), Container Index(CI) and Bretaeau Index (BI) in the Village District Gedongkiwo Mantrijeron Yogyakarta SpecialProvince of Yogyakarta.Methods: This was qualitative descriptive research. Samples in this study were 100 houses ineach RW 02, 06 and 09 in the Village Gedongkiwo. Data obtained by the survey to eachhousehold to determine HI, CI, and BI by filling out a check list sheet. Data analysis of theresults of research carried out in accordance with two criteria: If HI> 10% category of